Annual review of health care management strategy and policy perspectives on reforming health systems - Friedman, Leonard H.; Savage, Grant T. 1954-; Goes, Jim (Advances in health care management, 2012)
System wide health reform has become the norm across the globe, forcing health care delivery organizations to critically examine the ways in which they are structured and operate on a day to day basis. Resource scarcity has become common while at the same time, quality and clinical outcomes become the basis upon which these organizations are measured and compared with one another. This volume of "Advances in Health Care Management" includes contributions from key academic thought leaders from around the world who critically examine how health reform impacts the macro, meso and micro level strategy and policy decisions of healthcare organizations.